Pengaruh Kualitas Pelayanan dan Kompetensi Pegawai Terhadap Kepuasan Pengguna Jasa Pada Dinas Pemberdayaan Masyarakat dan Desa Kabupaten Katingan - Hygia Altonie; Lelo Sintani; Tonich Uda; Yunikewaty Yunikewaty; Usup Riassy Christa; Yohanes Joni Pambelum (Journal Pendidikan Ilmu Pengetahuan Sosial, 2022)
The Community and Village Empowerment Service is the implementing element of Government Affairs in the Community and Village Empowerment Sector which is the regional authority. Implementation of the duties and functions of the Community and Village Empowerment Service as the Implementer of Local Government in the field of Community and Village Empowerment, various efforts have been made by the Leaders, starting from the Staff, Head of Section, Head of Division to the Head of the Katingan Regency Village Community Empowerment Service to spur service and competency improvements. However, all of this has not produced results or has a significant effect on improving employee services. This may be due to a complete lack of competence on how to improve employee services. The problems are as follows: 1) The quality of service is still low at the Katingan Regency Community and Village Empowerment Service. 2). Employee competence is still low in carrying out tasks/jobs at the Community and Village Empowerment Service. 3) Low employee work discipline can be seen from the inaccuracy of employees in using working hours and the absence of attendance (presence) which results in employees not being on time when leaving and coming home from work. This research aims are: 1). To analyze the effect of service quality on service users at the Katingan Regency Community and Village Empowerment Service. 2). To analyze the effect of employee competence on service user satisfaction at the Katingan Regency Community and Village Empowerment Service. This study uses a survey with a research instrument in the form of a questionnaire distributed to respondents. In collecting questionnaires through the process, researchers in collecting primary data with survey methods through research instruments (questionnaires) of all village governments in Katingan Regency with a research sample of 115 respondents. The research site is in Katingan Regency. Primary and secondary data sources, data collection methods used literature study (documentation), and questionnaires. The analytical tool used in this study is the PLS (partial least square) based SEM (structure equation model) method. The results of this study indicate that: The results of testing the effect of service quality on increasing service user satisfaction can be proven by looking at the estimated path coefficient value of 0.115 with a critical point value (t-statistic) of 0.618 (<1.96) or a P-value of 0.000 greater than = 0.05 which means it is not significant. The results of testing the effect of competence on increasing service user satisfaction can be proven by looking at the estimated path coefficient value of 0.763 with a critical point value (t-statistic) of 4.271 (> 1.96) or P-value 0.000 smaller than = 0.05 which means significant.